Impact of Organizational Justice and Leader-Member Exchange Behavior on Turnover Intentions and Extra Role Behavior - Sarwar, Huma (Advances in Social Sciences Research Journal, 2017)
Work occupies a significant place in people’s lives, and not only because it provides income, challenges and relationships. The conditions under which people work have profound implications for their physical and emotional well-being (Guest, 2004; Moorman, 1991; Namie & Namie, 2000). The purpose of this project is to investigate the relationship of organizational justice, leader member exchange behavior and organizational citizenship behavior on turnover intentions in banking sector of Pakistan. To investigate the said relationships, 200 questionnaires will be collected from the banking industry of Pakistan. Multiple analyses will be performed including factor analyses, regressions, correlations and other descriptive statistics.